Analisis Putaran Motor Induksi 3 Phasa Pada Electrical Submersible Pump dengan Menggunakan Metode Fuzzy Tsukamoto - Marjulis, Nofriandi; Zondra, Elvira; Yuvendius, Hazra (Teknik Elektro Universitas Lancang Kuning, 2023)
The method for lifting on an artificial system is by using an Electrical Submersible Pump (ESP), where a three-phase induction motor has two poles as the driving force. The motor is connected to the shaft so that the motor will rotate, and the impeller part of the pump will rotate to lift the fluid to the holding tank. In determining the pump rotation so that the motor works in normal conditions where the frequency value is taken in the calculation of the ratio of the motor changes to the frequency with a value of 53 Hz, the rotor rotation value (Ns) is 3,180 rpm and the rotor speed (Nr) is 3,100.5 rpm, at a frequency of 3,100 rpm. 56 Hz the rotor rotation value (Ns) is 3,600 rpm and the rotor speed (Nr) is 3,270 rpm. Determine the amount of fluid flow by calculating the actual flow rate with the calculated flow rate at a frequency of 53 Hz. The results of this study obtained an error value of 1.81%, at a frequency of 55 Hz an error value of 7.5% was obtained and at a frequency of 58 Hz was 8.7%. Then the results of the comparison of calculations with the Tsukamoto method simulation with a working fluid level of 1,254 feet and a fluid flow rate of 1,072 PFPD, so that the frequency value at VSD is 55.5 Hz.